Effectiveness of Regional Regulation Implementation in Guidance and Protection of Street Vendors in Manokwari Regency: A Study of Policy Analysis and Socio-Economic Impacts - Setitit, Paskalina; Roberth KR Hammar; Carina Budi Siswani (Manunggal Halim Jaya, 2025)
This study aims to assess the effectiveness of the implementation of Manokwari Regency Regional Regulation Number 15 of 2021 concerning the Arrangement and Empowerment of Street Vendors (PKL) and its socio-economic impact on these micro-enterprises. As the capital of West Papua Province, Manokwari Regency is experiencing rapid population growth and urbanization, which impacts the dynamics of urban space and increases street vendor activity in strategic public spaces. This regional regulation is expected to be an instrument that not only regulates street vendors' physical and legal existence but also empowers them to transform into independent and competitive formal business actors. However, this study found that implementing the Regional Regulation still faces significant obstacles, such as low legal awareness and understanding among street vendors, suboptimal coordination between government agencies, and locations for street vendor relocations that are considered less strategic and impact the sustainability of their businesses. This creates a gap between written legal norms (law on the books) and actual practice (law in action), resulting in less than optimal guidance and protection for street vendors. The socio-economic impacts of implementing the Regional Regulation are also diverse. On the one hand, street vendors (PKL) significantly support the informal economy and reduce unemployment in Manokwari Regency. On the other hand, the less participatory arrangement and the dominance of a repressive approach create uncertainty and resistance among street vendors, which impacts their income stability and engagement in development programs. This study emphasizes the importance of a more integrated, participatory, educational, and empowering approach and increased synergy between agencies to ensure inclusive and sustainable policy implementation. The research methodology employed a qualitative approach, collecting data through semi-structured interviews, participant observation, and official document analysis. Data analysis used manual reduction and coding techniques to identify key themes. Validity and reliability were maintained through data triangulation and member checking. The results of this study are expected to provide strategic policy recommendations for the development and protection of street vendors (PKL), which can harmonize urban development needs with the welfare of micro-communities, particularly in autonomous regions with unique socio-cultural characteristics such as West Papua.